Obraz wsi wołogodzkiej w powieści Przeddzień Wasilija Biełowa - Rutkowska, Andżelika (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This article is aimed at reviewing of the novel Eves by Vasilii Belov to find a connection between the Vologda's region and the work. The Author devotes a particular attention to the space and the social order that are shown in the novel. He also emphasizes and describes traditions, customs, merits and characters' perception of the world. The analysis demonstrates the description of the Vologda's region in the Belov's novel proves it's special features that make this area different from the other regions of Russia. Also there are some circumstances of the novel's appearance and publication in the article.